Different temporal trends of exposure to Bisphenol A among international travelers between Los Angeles and Beijing. (August 2020) - Lin, Yan; Qiu, Xinghua; Liu, Jinming; Tseng, Chi-Hong; Allard, Patrick; Araujo, Jesus A.; Zhu, Yifang
Graphical abstract: Highlights: BPA exposure was assessed among 55 travelers between Los Angeles and Beijing. Traveling from Los Angeles to Beijing increases exposure to BPA. Exposure to BPA was decreased in Los Angeles from 2012 to 2017, but not in Beijing. Potential drivers of the BPA exposure temporal trend are discussed. Abstract: Recent studies suggested a significant downward trend in population's exposure to bisphenol A (BPA) in the United States. However, the temporal trend of BPA exposure remains unclear in China - a populous country with substantial industrial activities but less efforts made to phase out BPA in consumer products. In addition, it is unclear to what extent a visit from the United States to China could affect human exposure to BPA. In this natural experiment, we measured the concentration of total BPA in 418 urine samples repeatedly collected from 55 Los Angeles residents before, during, and after they spent 10 weeks in Beijing from 2012 to 2017. We found that traveling from Los Angeles to Beijing led to a 2.91-fold (95% CI: 2.43 to 3.50) increase in urinary BPA levels, which fully returned to baseline after study participants came back to Los Angeles. From 2012 to 2017, urinary BPA concentrations decreased in Los Angeles by 25.5% per year (95% CI: −30.8% to −19.8%; p  < 0.001) but did not change in Beijing ( p  = 0.24). Consequently, the concentration ratio of urinary BPA between Beijing and Los Angeles increased from 1.23 (95% CI: 0.82 to 1.85) in 2012 to 4.05 (95% CI: 2.75 to 5.97) in 2017. These results indicate that BPA exposures may increase among international travelers to China. Additional efforts are needed to reduce population's exposure to BPA in China.